HE EFFECT OF HORSERADISH PEROXIDASE (HRP)-DEXTRAN CONJUGATE ON NAPHTOL BLUE BLACK - Onder, R. Selva; Celebi, Mithat; Altikatoglu, Melda; Kuzu, Huriye (YILDIZ TECHNICAL UNIV, 2009)
The removal of azo dye Naphtol Blue Black in aqueous media with the catalysis of HRP-dextran conjugate was studied. HRP was purified by affinity chromatography using immobilized Con A. Enzyme-dextran conjugate with 1/10 molar ratio was synthesized using dextran aldehyde derivative (Dextran Mw 75.000 Da) and purified enzyme. The reaction was carried out at pH 3, 4, 5, 6, 7 and 8 in a 25, 30, 35, 40, 45, 50, 60, 70 degrees C temperatured crystal cuvette of UV-Vis spectrophotometer. The bleaching of the dye depending on the time was observed with the absorption spectra recorded regularly for one hour. The best results were obtained at pH 4 and 5 for all temperatures studied.
Keywords: HRP; dextran; conjugate; naphtol blue black; dye bleaching; DEGRADATION; ENZYMES; DYES; PURIFICATION; WATER; Engineering